Ochrona konsumenta zawierającego umowy elektroniczne - Sobczak, Marlena (Wydawnictwo C.H. Beck, 2022)
The purpose of this study is to present the protection mechanisms used by the legislator to protect the consumer, who is the weaker party to contracts concluded, in particular, by means of electronic communication. Therefore, the task of this paper is to present a definition of the concept of a consumer, outline the obligations of an entrepreneur constituted on the grounds of the provisions on consumer rights, and outline the applicable regulations relating to prohibited contractual clauses. The above issues will be presented in relation to a category of contracts, differentiated by the legislator, concluded online, i.e. electronic contracts.
Keywords: electronic contracts; consumer; consumer protection; distance contracts